A COMPARATIVE STUDY OF DIAGNOSTIC ACCURACY RATE AND UNIMAGED RATE OF MAMMOGRAPHY FOR BREAST CANCER - KOIKE, Yasuo; TERAI, Naoki (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2001)
A series of 686 women with breast cancer who underwent mammographic examination were subjected. The subjects were divided into five groups {T(+), C(+), TC(+), A(+) and TCA(-)} according to the presence or absence of mass density (T), microcalcification (C) or architectual distortion (A) on mammogram. Diagnostic accuracy rate (DAR) and unimaged rate (UIR) of mammography were investigated and the following results were obtained. (1) DRA of mammography between different mammographic apparatus was no significant difference, but UIR was significantly difference among them. (2) DAR according to mammographic findings was the highest in TC(+) group, follwed by C(+), T(+) and A(+) group. (3) UIR under 40's was significantly higher and DAR was significantly lower than those over 50's (4) UIR under 2.0cm in tumor size was significantly higher and DAR was significantly lower than those over 2.1cm. (5) UIR of unclassified type was the highest in all types. DAR of unclassified type and circumscribed type were signifiacantly lower than those of infiltrative type and intermediate type. (6) DAR of noninvasive carcinomas were significantly lower than those of invasive ductal carcinomas. (7) UIR of the group of negative lymph node metastasis was significantly higher and DAR was significantly lower than those of the positive group. (8) To raize DAR of mammography was needed to decrease UIR.